Polyphenol‐Containing Nanoparticles: Synthesis, Properties, and Therapeutic Delivery - Guo, Yuxin; Sun, Qing; Wu, Fu‐Gen; Dai, Yunlu; Chen, Xiaoyuan (Advanced materials (Weinheim), 2021)
Polyphenols, the phenolic hydroxyl group‐containing organic molecules, are widely found in natural plants and have shown beneficial effects on human health. Recently, polyphenol‐containing nanoparticles have attracted extensive research attention due to their antioxidation property, anticancer activity, and universal adherent affinity, and thus have shown great promise in the preparation, stabilization, and modification of multifunctional nanoassemblies for bioimaging, therapeutic delivery, and other biomedical applications. Additionally, the metal−polyphenol networks, formed by the coordination interactions between polyphenols and metal ions, have been used to prepare an important class of polyphenol‐containing nanoparticles for surface modification, bioimaging, drug delivery, and disease treatments. By focusing on the interactions between polyphenols and different materials (e.g., metal ions, inorganic materials, polymers, proteins, and nucleic acids), a comprehensive review on the synthesis and properties of the polyphenol‐containing nanoparticles is provided. Moreover, the remarkable versatility of polyphenol‐containing nanoparticles in different biomedical applications, including biodetection, multimodal bioimaging, protein and gene delivery, bone repair, antibiosis, and cancer theranostics is also demonstrated. Finally, the challenges faced by future research regarding the polyphenol‐containing nanoparticles are discussed. The synthesis, properties, and biomedical applications of polyphenol‐containing nanomaterials are comprehensively reviewed. The problems in the current polyphenol‐based nanosystems and the future research directions in this field are also discussed.